2017
DOI: 10.1038/bjc.2017.165
|View full text |Cite
|
Sign up to set email alerts
|

KIF15 promotes pancreatic cancer proliferation via the MEK–ERK signalling pathway

Abstract: Background:Pancreatic cancer is highly malignant and characterised by rapid and uncontrolled growth. While some of the important regulatory networks involved in pancreatic cancer have been determined, the cancer relevant genes have not been fully identified.Methods:We screened genes that may control proliferation in pancreatic cancer in seven pairs of matched pancreatic cancer and normal pancreatic tissue samples. We examined KIF15 expression in pancreatic cancer tissues and the effect of KIF15 on cell prolife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
82
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(86 citation statements)
references
References 40 publications
4
82
0
Order By: Relevance
“…It works on chromosome division by moving on microtubules . Previous reports indicate that KIF15 acts on tumor proliferation through the MEK‐ERK pathway and its expression levels in pancreatic cancer and breast cancer tissues are positively correlated with poor prognosis . NUF2 belongs to the NDC80 complex involving NDC80, spindle pole body component 24 (SPC24), and spindle pole body component 25 (SPC25) and functions as a kinetochore protein .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It works on chromosome division by moving on microtubules . Previous reports indicate that KIF15 acts on tumor proliferation through the MEK‐ERK pathway and its expression levels in pancreatic cancer and breast cancer tissues are positively correlated with poor prognosis . NUF2 belongs to the NDC80 complex involving NDC80, spindle pole body component 24 (SPC24), and spindle pole body component 25 (SPC25) and functions as a kinetochore protein .…”
Section: Discussionmentioning
confidence: 99%
“…21 Previous reports indicate that KIF15 acts on tumor proliferation through the MEK-ERK pathway and its expression levels in pancreatic cancer and breast cancer tissues are positively correlated with poor prognosis. 22,23 NUF2 belongs to the NDC80 complex involving NDC80, spindle pole body component 24 (SPC24), and spindle pole body component 25 (SPC25) and functions as a kinetochore protein. 24 NUF2 is reported as one of the cancer testis antigens which is ectopically secreted by cancer, and the expression levels of NUF2 is elevated in prostate cancer tissues.…”
Section: Kif15 Is a Motor Protein That Acts On Cell Division And Belongsmentioning
confidence: 99%
“…It has been reported that KIF15 is induced by estrogen and that its upregulation, together with ANCCA that is also induced by estrogen, is associated with breast cancer cell growth, survival, and resistance to tamoxifen [14]. Recently, KIF15 was found to be overexpressed in pancreatic cancer, where it promotes tumor cell proliferation via the MEK-ERK signaling pathway [15]. Bidkhori et al reconstructed a "genome-scale co-expression network" [16] to test their bioinformatics-derived prediction that KIF15 is overexpressed in LUAD and that it may be important for cell cycle regulation.…”
Section: Introductionmentioning
confidence: 99%
“…This redundancy between Kif15 and Eg5 is of interest as a potential factor in the disappointing ineffectiveness thus far of Eg5 inhibitors as cancer therapeutics (Tanenbaum et al , 2009;Rath and Kozielski, 2012;Milic et al , 2018;Dumas et al , 2019) . It is particularly notable since Kif15 overexpression results in lagging chromosomes (Malaby et al , 2019) , and is upregulated in a number of cancers (Ma et al , 2014;Wang et al , 2017;Qiao et al , 2018;Yu et al , 2019;Zhao et al , 2019;Sun et al , 2020;Terribas et al , 2020) . Under normal circumstances, however, Kif15 localizes predominantly to k-fiber microtubules.…”
Section: Introductionmentioning
confidence: 99%
“…This redundancy between Kif15 and Eg5 is of particular interest as a potential factor in the disappointing ineffectiveness thus far of Eg5 inhibitors as cancer therapeutics (Tanenbaum et al 2009;Milic et al 2018;Dumas et al 2019;Rath and Kozielski 2012) . Furthermore, Kif15 upregulation is found in a number of cancer types and can result in rapid cancer cell proliferation (Wang et al 2017;Zhao et al 2019;Yu et al 2019;Qiao et al 2018;Sun et al 2020;Terribas et al 2020;Ma et al 2014) . Under normal circumstances, however, Kif15 localizes predominantly to k-fiber microtubules.…”
Section: Introductionmentioning
confidence: 99%